Expanding the coverage of illegal economic activities in national accounts - Ilcho Bechev (Eurostat Review on National Accounts and Macroeconomic Indicators (EURONA), 2018)
This paper discusses a theoretical possibility of expanding the coverage of illegal economic activities (IEAs) in possible areas that go beyond the minimum recommendations adopted in a number of European countries. It also investigates the relevance and sources for statistics on additional IEAs within national accounts. The study further suggests that a broad set of IEAs under the heading of online services could be of interest in terms of their economic significance and that this area may be worthy of further investigation.
Keywords: E01; E23; E26; 330; national accounts; illegal economic activities; methodology; estimation